Validitas Lembar Kerja Peserta Didik (Lkpd) Berbasis Discovery Learning Pada Materi Sistem Peredaran Darah Untuk Peserta Didik Kelas Viii SMP/MTs - Idrus, Hanifah Aniswah; Lufri, Lufri; Syamsurizal, Syamsurizal; Fuadiyah, Sa’diatul (JURNAL PENDIDIKAN ROKANIA; Vol 7 No 3 (2022): Jurnal Pendidikan Rokania, 2022)
This study aims to develop discovery learning-based worksheets on the circulatory system material that is suitable for use in learning activities for class VIII students. Discovery learning is a learning model in which students can play an active role in the learning process and are able to find concepts from learning materials. This research includes the type of research and development (Research and Development). The research procedure used in the development of discovery learning-based worksheets uses a 4-D model from Thiagarajan, Semmel and Semmel, namely 4 stages of development, namely define (defining stage), design (planning stage), develope (development stage), and disseminate (dissemination stage). ). Given the limitations of time and cost, this research is limited to only being carried out until the develop stage. So it can be concluded that the development of discovery learning-based worksheets on the circulatory system material for use in class VIII SMP/MTs students that was developed is very valid to be used later in learning